Mitochondrial Morphology and Mitophagy in Heart Diseases: Qualitative and Quantitative Analyses Using Transmission Electron Microscopy - Collins, Helen E.; Kane, Mariame Selma; Litovsky, Silvio H.; Darley-Usmar, Victor M.; Young, Martin E.; Chatham, John C.; Zhang, Jianhua (Frontiers in Aging, 2021)
Transmission electron microscopy (TEM) has long been an important technique, capable of high degree resolution and visualization of subcellular structures and organization. Over the last 20 years, TEM has gained in popularity in the cardiovascular field to visualize changes at the nanometer scale in cardiac ultrastructure during cardiovascular development, aging, and a broad range of pathologies. Recently, cardiovascular TEM enabled the studies of several signaling processes impacting mitochondrial function, such as mitochondrial fission/fusion, autophagy, mitophagy, lysosomal degradation, and lipophagy. The goals of this review are to provide an overview of the current usage of TEM to study cardiac ultrastructural changes, how TEM aided the visualization of mitochondria, autophagy, and mitophagy under normal and cardiovascular disease conditions, and to discuss the overall advantages and disadvantages of TEM, as well as potential future capabilities and advancements in the field.